Iraq : Staff Report for the 2015 Article IV Consultation and Request for Purchase Under the Rapid Financing Instrument. (IMF Staff Country Reports; Country Report, 2015)
This 2015 Article IV Consultation highlights that Iraq is facing a double shock emerging from the ISIS insurgency and the plunge in global oil prices. In 2014, real GDP contracted by 2.1 percent mainly owing to the impact of the conflict, while oil production and exports increased slightly compared with 2013. In 2015, overall economic activity is expected to see a modest recovery of 0.5 percent thanks to oil sector expansion, while non-oil activity is expected to contract further. Medium-term growth prospects remain positive, though less favorable than before the crisis. Growth will be driven by the projected ramp-up in oil production and the rebound in non-oil growth supported by the expected improvement in security and implementation of structural reform.